Envisaging the use of evidence‐based practice (EBP): how nurse academics facilitate EBP use in theory and practice across Australian undergraduate programmes. Issue 17 (25th April 2017) - Malik, Gulzar; McKenna, Lisa; Griffiths, Debra
Abstract : Aims and objectives: This paper is drawn from a grounded theory study that aimed to investigate processes undertaken by academics when integrating evidence‐based practice into undergraduate curricula. This paper focuses on how nurse academics facilitated students to apply evidence‐based practice in theory and practice. Background: Facilitating undergraduate nursing students to develop skills within an evidence‐based practice framework is vital to achieving evidence‐based care. Studies on evidence‐based practice conducted globally suggests that there is a need to investigate approaches used by nurse academics in facilitating students' understanding and use of evidence‐based practice during their nurse education. Methods: Employing constructivist grounded theory approach, 23 nurse academics across Australian universities were interviewed and nine observed during their teaching. Some study participants shared their unit guides to enrich analysis. Data analysis was performed by following Charmaz's approach of coding procedures; as a result, four categories were constructed. This paper focuses on the category conceptualised as Envisaging the use of evidence‐based practice . Results: Findings revealed that most academics‐assisted students to use evidence in academic‐related activities. Recognising the importance of evidence‐based practice in practice, some also expected students to apply evidence‐based practice during clinical experiences. However, the level of students' appreciation for evidence‐based practice during clinical experiences was unknown to participants and was influenced by practice‐related barriers. Acknowledging these challenges, academics were engaged in dialogue with students and suggested the need for academia–practice collaboration in combating the cited barriers. Conclusion: Ensuring academics are supported to emphasise clinical application of evidence‐based practice requires strategies at school and practice levels. Faculty development, engagement of clinical nurses with evidence‐based practice, supportive culture for nurses and students to apply evidence‐based practice principles, and collaboration between academia and practice will make facilitation by academics practical and meaningful for students. Relevance to clinical practice: Findings from this study point to a number of initiatives for clinical leadership to provide infrastructure and support for academics, practising nurses and undergraduate students to adopt evidence‐based practice in practice settings, thereby influencing practice outcomes.